HAS LEAN MANUFACTURING REMAINED RELEVANT IN THE LAST HALF A DECADE? - Mohamad Zaidi, Muhammad Khairul Hamizan; Mohamad , Effendi; Abd Rahman, Mohd Soufhwee; Muhammad Shafee, Nur Ain Qistina; Abd Shukor, Mohd Hamdi; Ito, Teruaki (Journal of Human Capital Development (JHCD), 2024)
The Lean Manufacturing (LM) approach is founded on two fundamental principles: producing high-quality products at low production costs and satisfying customer demands. Toyota Motor Company introduced LM in the 1940s. With the advancement of technology, a wide range of products need to be efficiently produced to contend with various organisations. This study attempts to determine the significance of LM application in the industries through the last 5 years (2018-2023), using "LM" as the keyword for searching the published studies. The researchers identified 119 research articles using the PRISMA literature review process. After reviewing the papers, they recognised that LM was still relevant even today since the traditional LM tools can resolve 8 waste-related issues noted in the manufacturing line. These problems could be solved by combining the Simulation (SM) process with the Internet of Things (IoT4.0). Keywords: IoT 4.0, lean manufacturing, PRISMA, simulation, waste